Improved sensory acceptance and cytotoxicity to breast cancer cell line of instant germinated black rice yogurt supplemented with gellan gum - Mongkontanawat, Naruemon; Khunphutthiraphi, Thongjuan (Food Agricultural Sciences and Technology, 2022)
Various concentrations of gellan gum (e.g. 0.00, 2.50, 5.00, 7.50 and 10.00) were supplemented in instant germinated native black rice yogurt. After rehydration with the ratio of instant yogurt: water (1:10), then the properties of product were evaluated. Our results revealed that the concentration of gellan gum affected to the color (L*, a*,b*), pH and consistency of the yogurt. However, concentration of gellan gum did not affect to moisture content, total soluble solid and total viable count. From sensory evaluation with a 9-point hedonic scale, the gellan gum slightly increased color, odor, flavor and sharply increased texture and overall acceptability of yogurt. The addition of 10% (w/w) gellan gum resulted in the highest texture and overall acceptability scores (p≤0.05). Therefore, this treatment was selected to assess the properties compared with a control. Gellan gum did not affect the chemical composition including moisture content, protein, lipid, fiber, ash, total carbohydrate, g-aminobutyric acid, DPPH antioxidant property, total soluble solid, total viable count and yeast and mold count. Moreover, results from Fourier Transform Infrared Spectroscopy (FTIR) analysis indicated that both control and instant germinated native black rice yogurt had similar transmission of spectra. Interestingly, this instant germinated black rice yogurt showed powerful toxicity to breast cancer cell line (MDA-MB-231) which was higher than in the control (without gellan gum). This finding suggested that these instant germinated native black rice yogurts could be served as a healthy alternative functional meal for general consumers, especially adults and elderly.